2021
DOI: 10.18502/fem.v5i3.5891
|View full text |Cite
|
Sign up to set email alerts
|

Seven Criteria of Severe COVID-19 (SCSC): A New Pre-Hospital Prognostic Scoring Tool Suggested for Screening of Probable/Confirmed COVID-19 Patients with Severe Outcomes

Abstract: Introduction: COVID-19 pandemic led to various consequences in medical care that had been long provided for the patients referred to the hospitals. Objective: We conducted this study to derive and validate a new scoring system that can accurately differentiate COVID-19 patients who may have a worse outcome from others at the prehospital stage. Methods: This study was performed on probable/confirmed COVID-19 patients, who were transferred to the hospitals by Tehran emergency medical services (EMS). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…According to their findings, initial vital signs (with the exception of body temperature) [ 82 ], prehospital triage tools [ 81 ], and telephone screening processes/surveillance tools used by emergency medical dispatchers [ 46 , 65 , 77 , 80 ] had little to moderate predictive value for the identification of COVID-19 patients and/or death.…”
Section: Resultsmentioning
confidence: 99%
“…According to their findings, initial vital signs (with the exception of body temperature) [ 82 ], prehospital triage tools [ 81 ], and telephone screening processes/surveillance tools used by emergency medical dispatchers [ 46 , 65 , 77 , 80 ] had little to moderate predictive value for the identification of COVID-19 patients and/or death.…”
Section: Resultsmentioning
confidence: 99%
“…The NEWS is widely used in clinical practice. Furthermore, in the context of COVID‐19, the NEWS has so far been evaluated, 6 , 7 , 8 but the population of these studies were selected from March 2020 to April 2020 when the Delta variant did not exist. In this study, compared with COVID‐19 wild type, the NEWS showed comparable prediction accuracy for severe disease caused by the Delta variant.…”
Section: Discussionmentioning
confidence: 99%
“…Traditional clinical risk stratification tools are widely used for triage and continuous assessment of patients with severe infectious diseases. Several studies have evaluated the use of these tools in patients with SARS‐CoV‐2 infection with variable results 6–11 . Furthermore, it has been confirmed that the severity prediction ability of the National Early Warning Score (NEWS) 6–8 and NEWS2 9,10 is significant.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation